Patterns and predictors of anaemia in haemodialysis patients: relationship with comorbidities and dialysis exposure time - Handrean, I Gede Eka; Putra MN, I Made Mahadinata; Pratama Putra, I Gede Laksmana (Universitas Muhammadiyah Purwokerto, 2025)
Background: Anaemia is a common and serious complication in patients with chronic kidney disease (CKD) undergoing haemodialysis, contributing to increased morbidity, mortality, and reduced quality of life. Its prevalence and predictors vary across populations, and evidence from Indonesian cohorts remains limited. Objective: This study aimed to investigate the prevalence, severity, and predictors of anaemia in haemodialysis patients, with a particular focus on the influence of comorbidities and dialysis duration. Methods: A cross-sectional analytic study was conducted among 71 CKD patients undergoing regular haemodialysis at Kenak Medika Ubud Hospital between July and August 2024. Data on demographics, dialysis duration, comorbidities, and laboratory parameters (Hb, BUN, SC, MCV, MCH) were extracted from medical records. Anaemia severity was classified according to WHO and KDIGO guidelines. Statistical analysis included descriptive statistics, Chi-square tests, ANOVA, correlation analysis, and multivariate linear regression. Results: The prevalence of anaemia was 70.4%, with moderate anaemia being the most common presentation (52.1%). Patients with dialysis duration >24 months had significantly lower haemoglobin levels compared to those with shorter treatment exposure (p = 0.014). Multivariate regression analysis identified hypertension (p = 0.009) and cardiovascular disease (p = 0.013) as significant predictors of haemoglobin levels, while diabetes mellitus, BUN, SC, MCV, and MCH showed no significant associations. Conclusion: Anaemia remains highly prevalent in haemodialysis patients, with dialysis duration and cardiovascular comorbidities emerging as key predictors. These findings underscore the importance of routine anaemia monitoring, individualized treatment strategies, and integrated management of cardiovascular comorbidities to optimize outcomes in haemodialysis populations.